2015
DOI: 10.1073/pnas.1508820112
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering tissue-induced Klebsiella pneumoniae lipid A structure

Abstract: The outcome of an infection depends on host recognition of the pathogen, hence leading to the activation of signaling pathways controlling defense responses. A long-held belief is that the modification of the lipid A moiety of the lipopolysaccharide could help Gram-negative pathogens to evade innate immunity. However, direct evidence that this happens in vivo is lacking. Here we report the lipid A expressed in the tissues of infected mice by the human pathogen Klebsiella pneumoniae. Our findings demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
138
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(148 citation statements)
references
References 69 publications
(93 reference statements)
10
138
0
Order By: Relevance
“…K. pneumoniae demonstrates marked plasticity in its lipid A structure and in certain mammalian tissue sites, including the lungs, will switch to a 2-hydroxyacyl modification of its lipid A in a PhoPQ-regulated, LpxOdependent manner. In a manner similar to those of other bacteria that have modified LPSs, such as Yersinia, this modified lipid A does not activate the inflammatory response to the same degree as the native form of lipid A, effectively increasing the in vivo virulence of K. pneumoniae (260,263). Furthermore, the lipid A portion of K. pneumoniae LPS also plays a beneficial role in virulence, as a mutant strain of K. pneumoniae with altered lipid A acylation was attenuated in a mouse model of pneumonia.…”
Section: Lipopolysaccharidementioning
confidence: 85%
See 2 more Smart Citations
“…K. pneumoniae demonstrates marked plasticity in its lipid A structure and in certain mammalian tissue sites, including the lungs, will switch to a 2-hydroxyacyl modification of its lipid A in a PhoPQ-regulated, LpxOdependent manner. In a manner similar to those of other bacteria that have modified LPSs, such as Yersinia, this modified lipid A does not activate the inflammatory response to the same degree as the native form of lipid A, effectively increasing the in vivo virulence of K. pneumoniae (260,263). Furthermore, the lipid A portion of K. pneumoniae LPS also plays a beneficial role in virulence, as a mutant strain of K. pneumoniae with altered lipid A acylation was attenuated in a mouse model of pneumonia.…”
Section: Lipopolysaccharidementioning
confidence: 85%
“…Another method of preventing recognition by the immune response employed by some bacteria, such as Yersinia pestis, Helicobacter pylori, and Porphyromonas gingivalis, is modification of the LPS to a form that is no longer recognizable by certain immune receptors (260)(261)(262). Recent evidence suggests that K. pneumoniae may do the same (263). K. pneumoniae demonstrates marked plasticity in its lipid A structure and in certain mammalian tissue sites, including the lungs, will switch to a 2-hydroxyacyl modification of its lipid A in a PhoPQ-regulated, LpxOdependent manner.…”
Section: Lipopolysaccharidementioning
confidence: 99%
See 1 more Smart Citation
“…PhoPQ has been linked to modification of LPS and the outer membrane content (26)(27)(28) and regulates genes involved in colistin resistance, including pmrD and pmrAB (29,30). Mutations in PhoPQ in K. pneumoniae have already been shown to be associated with colistin and cationic peptide resistance and with lipid A modification (29,(31)(32)(33). Quantitative PCR (qPCR) analysis of strains with phoPQ mutations showed significant upregulation in the expression levels of phoPQ (at least 5-fold).…”
Section: Discussionmentioning
confidence: 99%
“…Two of the hydroxymyristoyl chains are further acylated with laureate (containing a C 12 backbone) and myristate (C 14 ) through the action of the late acyltransferases LpxL and LpxM, respectively (1). Pioneering studies demonstrated that Salmonella typhimurium remodels its lipid A by adding 4-amino-4-deoxy-L-arabinose and phosphoethanolamine to mask lipid A's negative charges, limiting its interaction with positively-charged antimicrobial peptides (2, 3), whereas Klebsiella pneumoniae produces a distinct lipid A in vivo to limit inflammation and to resist antimicrobial peptides and polymyxins (4). Although these remodeling events are therefore critical to understanding a variety of bacterial infections, most of the studies on lipid A remodeling have focused primarily on just a few bacterial species.…”
mentioning
confidence: 99%